2005
DOI: 10.1159/000090174
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Alcohol-Induced Hepatic Fibrosis

Abstract: Alcohol abuse is a major cause of liver fibrosis and cirrhosis in developed countries. Before alcoholic liver fibrosis becomes evident, the liver undergoes several stages of alcoholic liver disease including steatosis and steatohepatitis. Although the main mechanisms of fibrogenesis are independent of the etiology of liver injury, alcoholic liver fibrosis is distinctively characterized by a pronounced inflammatory response due to elevated gut-derived endotoxin plasma levels, an augmented generation of oxidativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 214 publications
1
61
0
2
Order By: Relevance
“…A lack of supplying blood vessels can compromise oxygen and nutrient delivery to tissue undergoing repair (31,32). Hypoxia has been shown to increase the production of collagen as well as profibrogenic factors like plasminogen activator inhibitor-1, tissue inhibitor of metalloproteinase-1, and connective tissue growth factor through an HIF-mediated transcriptional response (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…A lack of supplying blood vessels can compromise oxygen and nutrient delivery to tissue undergoing repair (31,32). Hypoxia has been shown to increase the production of collagen as well as profibrogenic factors like plasminogen activator inhibitor-1, tissue inhibitor of metalloproteinase-1, and connective tissue growth factor through an HIF-mediated transcriptional response (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Because TGF-β1 was implicated in suppression of NK cell activity 33 and HSCs are an important producer of TGF-β1 during HSC activation, 14,15 we investigated whether TGF-β1 was involved in the resistance to NK cell killing of ethanol HSCs. The RT-PCR analyses showed that expression of TGF-β1 mRNA was much stronger in ethanol HSCs than in pair HSCs ( Figure 7B), suggesting that ethanol HSCs produce more TGF-β1.…”
Section: Ethanol Hscs Are Resistant To Nk Cell Killing By a Tgf-β1-dementioning
confidence: 99%
“…11,12 In addition to simply enhancing liver injury, alcohol may accelerate progression of liver fibrosis through several mechanisms. [13][14][15] For instance, alcohol consumption may enhance hepatic HSC activation through an increase in gut-derived endotoxins, hypoxia (oxidative stress), or the formation of toxic and profibrogenic metabolites (eg, acetaldehyde or lipid peroxides). [13][14][15] Recently, we and others have shown that activation of the innate immune system, natural killer (NK) cells and interferon-γ (IFN-γ), inhibits liver fibrosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This event can be recapitulated in a culture model in which isolated HSCs are cultured on plastic in serumcontaining media. The activated HSCs are a rich source of type I and III fibrillar collagen and also secrete high levels of the tissue inhibitor of metalloproteinase 1 (TIMP-1) [3]. Many of the morphological and metabolic changes associated with HSC activation during fibrogenesis in vivo are also observed in HSCs grown in culture on plastic.…”
Section: Introductionmentioning
confidence: 99%